EXPLORING THE IMPACT OF SELF-REGULATED LEARNING STRATETGIES ON ENGLISH LANGUAGE MASTERY: A QUANTITATIVE ANALYSIS OF HIGH SCHOOL STUDENTS - Nofry Frans; Vera Wahani (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
ABSTRACT This study examines the relationship between self-regulated learning (SRL) strategies and English language mastery among senior high school students. Specifically, it investigates the overall effect of SRL on English achievement and identifies which specific SRL strategies serve as significant predictors of language proficiency. Using an adapted questionnaire from Magno (2010), SRL levels were measured among 400 students from grades XI and XII across Science and Social streams at X Senior High School, with a final sample size of 196 participants. Findings indicate that students demonstrated a high level of self-regulation in their learning, reflected in a mean SRL score of 2.83, and attained strong English achievement outcomes, with a mean score of 84.08. Statistical analysis confirms a significant effect of SRL on English achievement. However, the presence of heteroscedasticity prevented the application of multiple regression analysis, thereby limiting the identification of the strongest SRL predictors of English success. These results underscore the role of self-regulated learning in shaping academic achievement and highlight the need for further research into refining predictive models to better understand the impact of specific SRL strategies on language proficiency. Keywords: self-regulated, learning strategies, English mastery